Strategi Cerdas Pemanfaatan AI (Artificial intelligence) dalam Perencanaan Keuangan Berbasis Digital untuk Keberlanjutan UMKM: PKM - Munawarah, Israfil (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This community service aims to improve the financial digital literacy of Micro, Small, and Medium Enterprises (MSMEs) through the use of artificial intelligence (AI). By providing training and understanding of various AI-based tools that can be used for financial planning, it is hoped that MSMEs can optimize financial management, improve efficiency, and ultimately achieve business sustainability. This activity will include materials on analyzing financial data with AI, predicting market trends, and selecting the right digital financial solutions. Through the implementation of this technology, it is expected that MSMEs can manage their finances more effectively, strengthen their position in the market, and increase competitiveness in the digital economy.